Adapting to a new urbanizing environment: gendered strategies of Hanoi’s street food vendors - Kawarazuka, Nozomi; Béné, Christophe; Prain, Gordon (SAGE Publications, 2018)
Drawing upon examples of street vendors in Hanoi, this study explores gendered strategies to adapt to rapid urbanization, and how street vendors’ responses, in turn, shape the current informal food systems. The findings show that Hanoi’s informal food system is organized based on social, as well as economic, interactions and therefore the system’s power hierarchy and gender relations are different from those of formal systems, while providing livelihood opportunities for poor people in both urban and rural spaces. Women operate based on social relations rather than economic interactions, while men’s activities tend to be more capital-based and similar to the formal systems. As a result, men and women encounter different challenges in sustaining their activities in the face of policy and/or economic changes. The study concludes by highlighting adaptation capacity built upon social relations and describing the implications of integrating gender aspects for urban planning toward building more inclusive cities.